Analysing standardisation processes as technology trajectories in the mobile ecosystem: Implications for competition and innovation - Hanne Kristine Hallingby (International Telecommunications Society (ITS), 2014)
The traditional mobile industry expresses worries for the future due to converging technologies and new actors. Standards are the foundation for convergence, and have been central in all current subsectors of the mobile industry. However, subsectors have developed different technological knowledge, routines and path dependencies in their standardisation processes and can be understood as different technology trajectories within the same technology paradigm. The research question in this comparative case study is: What are characteristics, differences and similarities of important standardisation processes in the mobile telecommunication ecosystem? The systematic comparison suggests that the technology trajectories 3GPP and ETSI neither are able to spur necessary innovation in the wider ecosystem, nor to ensure satisfying profit. IETF and 3WC spur innovation through an extensive accessibility to standards, but appropriability conditions are challenging. It is private platforms such as Google and Apple that seem handle both aspects: to enable innovation and adoption by making technology elements public through extension markets, and simultaneously ensure profit by keeping technology private. This research contributes by clarifying how the tension between private and public goods is played out in major technology trajectories in the mobile telecommunication sector; especially helpful is the distinction between standard openness and extension markets as different means for making technology public. The four concepts developed for assessing the status of standardization processes can be used for structuring discussions on the issue, and for future analyses of technology innovations in the telecommunication sector.
Keywords: 330